Diversidad, estructura de especies forestales y su influencia en la regeneración natural de la microcuenca del estero Macul. Año 2013. Propuesta de recuperación. - Carbo Rivera, Esther Alexandra (2015)
In order to assess the diversity of forest species structure and its influence on the natural regeneration of the watershed Macul, an inventory of 80.86 ha of remaining forest was performed. It was divided into two blocks. To assess the adult mass (DBH> 7.5 cm) sample units of 20 m x 20 m (400 m2) were used. For natural regeneration sampling subunits 10 X 10 m (100 m2) for individuals with diameter greater than 2.5 and less than 7.5 cm, and sub-sampling of 2 x 2 m were established for species under 2.5 cm DAP. A sampling intensity of 5% (2400 m2) was applied; 3 sampling units (1200 m2) in each block. In addition a survey to obtain information on characteristics of the watershed Macul communities was performed. In blocks studied was obtained a total of 17 families, 21 genus, 22 species and 141 individuals with DBH> 7.5 cm. The largest number of genus, species and individuals was obtained in block 2. The most important families, according to the number of species were Fabaceae and Malvaceae, with three species each. The most abundant families were: Urtricaceae, Lamiaceae and Asteraceae. The greatest value of the Shannon diversity index was found in block 2. The species with the highest IVI was the teak, which is an introduced species; between native species with greater IVI were Cecropia peltata; Vitex gigantea; Vernonia. bacorcharoides; Erythrina poeppigiana and Ficus sp. In natural regeneration plots, a total of 92 individuals, 14 species, 14 genus and 12 families were reported. 2.5 cm - in block 1 the biggest number of families, genus, species and individuals in the group of plants of 7.50 was recorded. Only Lauraceae and Fabaceae family presented two species each; other species had a single species. The most abundant families in natural regeneration were Lauraceae and Poligonacea. In the vertical structure, the upper layer did not exceed 20 m and the middle stratum (7-14) was the one containing the largest number of trees. According to IUCN (Red Book of endangered species list, 2014), the species Cordia alliodora (laurel